Psychosocial Burdens of Hypertensive Patients (Medico Legal Update, 2020)
Hypertension is a major risk factor and antecedent of cardiovascular and end organ damage (myocardialinfarction, chronic kidney disease, descriptive design was conducted in Babylon city outpatients andhealth centers to identify psycho-social burdens of patients with hypertension,A questionnaire includingdemographic information and tow validated instruments assessing psychosocial burdens of hypertensivepatients,Data were collected through self-administration of questionnaire regarding the study,Data wereanalyzed through applying descriptive analysis as frequency, percentage, The participants had 43-48 yearsaged (45.1%) and were married (88.0%) with Not educated (52.2%) and (71.7%) were Male, the physicalindicators of sample weight 90 and more kg (50%) and height was 151-160 cm (38.6%) with normal BMI(38.0%).Patients face stress and each day and the lack of enough time to relax and the lack of a holiday in the middleof the week, lead them to suffer various health problems such specially hypertension.